Answer:
Explanation:
first you have to make this an improper fraction my multiplying -3 by 11 then add the product of that to 6 and put it all over 11
→
once you get this you have to do the reciprocal of this to get them to equal 1
→
![-(11)/(39)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ya968keebxkkf16t2pyfg91f45byiy60ye.png)
then multiply the number by the reciprocal
![-(39)/(11)* -(11)/(39)=(429)/(429)=1](https://img.qammunity.org/2021/formulas/mathematics/high-school/2mmwcypp76esf4zapzvief86plfmwyp24t.png)